Research of a fuzzy global sliding mode control scheme: A stability control scheme for anti-aircraft missile with swing nozzle thrust vector control. (March 2015) - Liu, Xiaodong; Zhang, Yu; Huang, Wanwei; Wang, Jianmin
In order to suppress the high-frequency chattering at control input in the premise of keeping robust against system uncertainties, a novel fuzzy global sliding mode controller (FGSMC) is proposed. A nonlinear switching function is designed in order that system trajectory can be set on sliding mode surface at initial time. A fuzzy decision maker, which can adaptively obtain the gain of signum term according to novel fuzzy logic, is proposed and introduced to guarantee the comprehensive properties with respect to the reachability of sliding mode and the smoothness of control input. Moreover, it possesses simple fuzzy inference rules and is easy to be realized in application. The FGSMC is employed to construct the stability control scheme for anti-aircraft missile with swing nozzle thrust vector control. Simulation results on researched anti-aircraft missile present that, in the existence of sustained disturbances, the proposed FGSMC scheme not only possesses better convergent performance, but also suppresses high-frequency chattering to a large extent, compared with conventional sliding mode control scheme.